Perencanaan Kawasan Wisata Danau Mawang Berbasis Konsep Creative, Smart, dan Sustainable Public Space - Iqbal Kamaruddin; Arifuddin Akil; Abdul Rachman Rasyid (Department of Urban and Regional Planning, Faculty of Engineering, University of Hasanuddin, 2021)
This plan aims to improve the quality of public spaces in Lake Mawang, Gowa Regency, South Sulawesi Province. In the Spatial Plan, Lake Mawang is included in the natural tourism development cluster. However, along with its development, this area is not organized and is experiencing environmental degradation. Based on the actual conditions of the area, efforts are needed to improve spatial quality, which can be started by making an area master plan with a creative, intelligent and sustainable public space planning concept. The main space components in planning this area include; cluster, transect, connection, center, parking, edges and diverse activities. The planning location is in Lake Mawang, Somba Opu District. The data used are primary and secondary data obtained from government agencies as well as observation, documentation and interviews. The analysis technique used is GAP analysis, spatial analysis fishnet grid ArcGIS, Analytical Hierarchy Process (AHP) and Performance Matrix Analysis (PMA) analysis. The main results of this plan are the master plan, the detailed plan for each component of the space based on creative, intelligent and sustainable concepts.